2015
DOI: 10.1261/rna.048785.114
|View full text |Cite
|
Sign up to set email alerts
|

EnD-Seq and AppEnD: sequencing 3′ ends to identify nontemplated tails and degradation intermediates

Abstract: Existing methods for detecting RNA intermediates resulting from exonuclease degradation are low-throughput and laborious. In addition, mapping the 3 ′ ends of RNA molecules to the genome after high-throughput sequencing is challenging, particularly if the 3 ′ ends contain post-transcriptional modifications. To address these problems, we developed EnD-Seq, a high-throughput sequencing protocol that preserves the 3 ′ end of RNA molecules, and AppEnD, a computational method for analyzing highthroughput sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 41 publications
(69 reference statements)
1
47
0
Order By: Relevance
“…The very 3 ′ end of the consensus binding site determined by CLIP-seq differs from the genomic sequence, with an enrichment of uridine in the last 2 nt. Recently, it was reported that a fraction of all histone mRNAs have the last 2-3 ′ encoded nucleotides replaced with uridines posttranscriptionally (Welch et al 2015) and we detected these 3 ′ ends present in the cell in our HITS-CLIP experiments.…”
Section: Analysis Of Crosslinking Datasupporting
confidence: 62%
See 4 more Smart Citations
“…The very 3 ′ end of the consensus binding site determined by CLIP-seq differs from the genomic sequence, with an enrichment of uridine in the last 2 nt. Recently, it was reported that a fraction of all histone mRNAs have the last 2-3 ′ encoded nucleotides replaced with uridines posttranscriptionally (Welch et al 2015) and we detected these 3 ′ ends present in the cell in our HITS-CLIP experiments.…”
Section: Analysis Of Crosslinking Datasupporting
confidence: 62%
“…Note that the x axis is the same for the boxplots (E,F) and the seqlogos (G,H) to display the sequence composition of the nuclease-resistant histone SL RNA fragments. (I) We used the AppEnD tool (Welch et al 2015) to identify nontemplated tails on the 3 ′ ends of histone RNA molecules present in HITS-CLIP reads. To avoid calling sequencing errors as tails, only reads that extended at least 4 nt into the 3 ′ adapter were analyzed.…”
Section: Mapping Inferred Nuclease Cleavage Sites Precisely Defines Tmentioning
confidence: 99%
See 3 more Smart Citations